Bruckner Red Light Reflex Test in a Hospital Setting - Saiju, R; Yun, S; Yoon, PD; Shrestha, MK; Shrestha, UD (Kathmandu University Medical Journal, 2013)
Background Childhood blindness is a major problem in developing world including Nepal that needs to be addressed. Objective The objective of study was to measure the effectiveness of the Bruckner red reflex test for screening of posterior segment opacities in children. Methods Patients aged less than five years who came to the Tilganga Institute of Ophthalmology, Kathmandu from March to August, 2009 were recruited in this cross-sectional descriptive study. Children were screened with the Bruckner red light reflex test in a dark room. Patients with abnormal Bruckner tests had their eyes dilated for further investigations. Abnormalities were recorded. The number of patients with an abnormal Bruckner test was recorded and correlated with their potential pathology. Results A total of 172 patients with 97 boys and 75 girls were included. Twenty-three had abnormal Bruckner test results in either one or both eyes. Four of these twenty-three patients had no pathology diagnosed; hence the sensitivity of the Bruckner screen to diagnose significant pathology was calculated at 82.6%. Of the 153 patients with normal results, two patients were found to have pathology detected, which included cataract and strabismus. Hence, the specificity of this test was 98.7%. The screening test had a positive predictive value of 90.5% and a negative predictive value of 97.4%. Conclusion Bruckner test screening is a sensitive and specific marker for detecting the posterior segment opacities in children. We recommend utilizing the test to evaluate these problems where other technologies are rare. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 23-26 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7338